The Emergence of Ideologies in the Post-Arab-Israeli Conflict: A Realist and Genealogical Geopolitical Analysis - Cahaya Mulyani Sakti; Mohammad Izdiyan Muttaqin; Hendra Kurniawan (Green Publisher Indonesia, 2026)
Beyond the Middle East, this confrontation has evolved into a major international political issue with profound global repercussions. The shifting regional landscape and the realignment of alliances underscore the deep geopolitical dimensions shaped by the conflict. Rather than serving as neutral mediators, several global political actors have viewed this confrontation as an arena to consolidate and expand their influence in the Middle East, further intensifying the escalation. This phenomenon has fostered the emergence of diverse ideological movements responding to the conflict, particularly to the colonization undertaken by Zionist forces. This study examines how the Arab-Israeli conflict has shaped the modern global political order through a historical lens, leading to the emergence and transformation of ideological currents. Employing a qualitative approach that integrates historical analysis, case study, and genealogical discourse analysis within the frameworks of classical realism and geopolitical theory, the research traces the evolution of ideologies on both sides of the conflict. The findings reveal a complex landscape of ideological responses, categorized into Arab resistance movements (Pan-Arabism, Anti-Colonialism, Marxism/Arab Socialism), religion-based movements (Hamas, Hezbollah, Jewish Anti-Zionism, Revisionist Zionism, Religious Zionism, Christian Zionism), and global movements (Neoconservatism, BDS). The study concludes that the Arab-Israeli conflict is not merely a territorial struggle but an ideological battle encompassing questions of identity, religion, and global power, which significantly complicates the pursuit of a just and lasting peace.